"We must help them despite who they are...": healthcare providers' attitudes and perspectives on care for young gay, bisexual and other men who have sex with men in Nairobi, Kenya - Samuel Waweru Mwaniki; Peter Mwenda Kaberia; Peter Mwangi Mugo; Thesla Palanee-Phillips (BMC, 2023)
Abstract Background Compared to young heterosexual men, young gay, bisexual and other men who have sex with men (YMSM) face a disproportionate burden of sexual health conditions. This disparity is occasioned by factors such as criminalization and stigmatization of same-sex practices, YMSM's limited access to non-judgmental and non-discriminatory health services, and challenges associated with healthcare delivery. We explored the attitudes and perspectives of tertiary academic institution-based healthcare providers (HCPs) toward provision of services to YMSM in Nairobi, Kenya. Methods In September 2021, six in-person focus group discussions (FGDs) were held with 36 HCPs drawn from six public tertiary academic institutions within the Nairobi metropolis. HCPs were drawn from six cadres: front office staff, nurses, clinicians, counsellors, laboratory technologists, and pharmaceutical technologists. Discussions were conducted in English, transcribed verbatim and analyzed thematically using NVivo version 12. Results Analysis showed that despite expressing disapproval of same-sex practices, HCPs recognized their professional duty to provide care to YMSM, voiced challenges they experienced when providing care to YMSM, and suggested possible strategies for improving care for YMSM. Disapproval of same-sex practices mainly stemmed from HCPs' personal values, societal norms and religious beliefs, though some HCPs identified religious principles such as the golden rule of "treating others as one would want to be treated" as motivation to providing care to YMSM. HCPs did not perceive criminalization of same-sex practices as a barrier to providing care to YMSM. Healthcare delivery challenges included inadequate knowledge and skills, a desire to "convert" YMSM's perceived deviant homosexual to the normative heterosexual orientation, secondary stigma from other HCPs, and healthcare settings that did not support YMSM to disclose same-sex practices. Suggestions for improving care comprised sensitization and training of HCPs, encouraging more HCP-YMSM interaction, providing YMSM-friendly and inclusive services, and advocacy for YMSM services. Conclusion There is need for interventions to improve HCPs' knowledge of YMSM's health needs, build skills to respond to these needs, and foster affirming attitudes toward same-sex practices. By so doing, YMSM can hopefully be able to access services that meet their needs, and are non-discriminatory, non-stigmatizing and non-judgmental.